98.5k views
0 votes
Someone please help me with example number two step-by-step full explanation and explain how to use the equation and how to rearrange it thanks

Someone please help me with example number two step-by-step full explanation and explain-example-1

1 Answer

0 votes

Given that the initial velocity is


\begin{gathered} V_o=\text{ 2.7 km/h} \\ =2.7*(5)/(18) \\ =0.75\text{ m/s} \end{gathered}

The acceleration is a = 0.40 m/s^2

The time is t = 3.6 s.

We have to find the final velocity, v.

The final velocity can be calculated by the formula


V_f=V_o+at

Substituting the values, the final velocity will be


\begin{gathered} V_f=0.75+0.40*3.6 \\ =2.19\text{ m/s} \end{gathered}

Thus, the final velocity is 2.19 m/s.

User Aggaton
by
5.7k points